Paradoks Kewajiban Bersaksi pada Ketentuan Hukum Acara Perdata - Zakki Adlhiyati (Departemen Hukum Perdata, 2018)
Analyzing witness obligation in giving testimony according to Indonesian civil procedural law is the objective of this writing. With the normative judicial method, concluded There is inconsistency in Indonesian civil procedural law in regulating the witness obligation. Punishment is provided for a witness when they neglected the hearing summons as regulated in Article 140 HIR/157 RBG, but in contrast article 143 HIR/170 RBG stated that no one may be forced to come before a court to testify in civil matters if the district court beyond their resides. Giving the same regulation with the current civil procedural law, the civil procedural law bill shows contradiction within its law and also with another law. Abandonment of court summons as a witness is a criminal offense with a sentence of six months in prison (Article 224 paragraph of the Criminal Code). The inconsistency and contradiction to some extent may bring negative impact to law enforcement and the law should be an amendment.